(untitled) (Journal of Telenursing (JOTING), 2023)
This study aims to analyze tepid sponge baths’ effect in reducing hyperthermic children’s body temperature. The research method used by Quasy is an experimental pre-test and post-test design. This study’s results show a significant change in pre-measurements in respondents with hyperthermic body temperature. The criteria for achieving body temperature within normal limits with the tepid sponge bath intervention for 10-15 minutes, the post-test results show a decrease in the average body temperature of respondents from 38.5℃ to 36.5℃ in 10 respondents, the results criteria were achieved. In conclusion, providing tepid sponge bath therapy effectively reduces body temperature in children who experience problems treating hyperthermia. Keywords: Hyperthermia, Childhood Concept, Increased Body Temperature, Tepid Sponge Bath